Surface photovoltage behavior of GaN columns. Issue 4 (3rd March 2015) - Deeb, Manal Ali; Wei, Jiandong; Hartmann, Jana; Wehmann, Hergo‐Heinrich; Waag, Andreas
<x xml:space="preserve">Abstract</x> GaN columns are grown by metal organic vapor phase epitaxy (MOVPE) with a high silane flow, which often leads to rough sidewalls and related problems during a subsequent shell overgrowth by e.g., InGaN/GaN quantum wells. In order to get more information on the surface of GaN columns before overgrowth, surface photovoltage (SPV) measurements have been performed by photo‐assisted Kelvin probe force microscopy (KPFM) before and after chemical etching of the surface. Its electronic properties are demonstrated to be influenced by the silane injection during the samples' growth. Distinct differences are shown in the SPV behavior of GaN columns before and after etching with phosphoric acid. SPV decreases before etching, whereas after etching it increases like that on GaN bulk material. Silicon related surface states introduced during the growth are considered as the origin of the SPV behavior of the as grown samples. The change of this behavior after etching is attributed to the removal of the Si containing surface coating. Our investigations not only show the important role of silane injection during the growth on the SPV behavior of GaN columns, but it also reveals that the photo‐assisted KPFM technique is an easy and quick method to analyze surfaces.